Analisis Quality of Service Pada Infrastruktur Jaringan Kantor Wilayah BPN Provinsi Papua - Pasaribu, Victor Ramos; Irjanto, Nourman Satya; Tatuhey, Emy Lenora (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
This study analyzes the quality of network service (Quality of Service/QoS) at the Papua Province National Land Agency (BPN) Regional Office by comparing two main network platforms, namely Mikrotik and Ruijie Cloud. Measurements are carried out with the main QoS parameters, namely throughput, packet loss, delay, and jitter, using Wireshark software referring to the TIPHON standard. Evaluation in three network usage scenarios, namely use during service, special service, and normal activities, to get an overview of network performance. The results of the study on the throughput parameter, Ruijie Cloud averaged 2,642 Mbps under normal conditions, higher than Mikrotik which only reached 2,149 Mbps. Packet loss parameters, Ruijie Cloud got lower packet loss (9.87%) compared to Mikrotik (16.13%) under normal conditions, indicating a better level of network stability. Delay parameters, Ruijie Cloud showed lower delays in general service conditions (4.03 ms) compared to Mikrotik (5,563 ms). In addition, the jitter on Ruijie Cloud is more stable, more suitable for use in low latency and high network stability applications.Keyword: Quality of Service; Wireshark; TIPHON; Mikrotik; Ruijie Cloud AbstrakPenelitian ini menganalisis kualitas layanan jaringan (Quality of Service/QoS) pada Kantor Wilayah Badan Pertanahan Nasional (BPN) Provinsi Papua dengan membandingkan dua platform jaringan utama, yaitu Mikrotik dan Ruijie Cloud. Pengukuran dilakukan dengan parameter utama QoS, yaitu throughput, packet loss, delay, dan jitter, menggunakan perangkat lunak Wireshark mengacu pada standar TIPHON. Evaluasi dalam tiga skenario penggunaan jaringan, yaitu penggunaan saat pelayanan, pelayanan khusus, dan kegiatan biasa, guna mendapatkan gambaran performa jaringan. Hasil penelitian pada parameter throughput, Ruijie Cloud rata-rata 2.642 Mbps dalam kondisi normal, lebih tinggi dibandingkan Mikrotik hanya mencapai 2.149 Mbps. Parameter packet loss, Ruijie Cloud mendapatkan packet loss yang lebih rendah (9.87%) dibandingkan Mikrotik (16.13%) dalam kondisi normal, menunjukkan tingkat kestabilan jaringan lebih baik. Parameter delay, Ruijie Cloud menunjukkan delay lebih rendah dalam kondisi layanan umum (4.03 ms) dibandingkan Mikrotik (5.563 ms). Selain itu, jitter Ruijie Cloud lebih stabil, cocok digunakan dalam aplikasi latensi rendah dan stabilitas jaringan tinggi.